(untitled) - Sarah, Hudson; Sabry, Shaaban (Business Expert Press, 2010)
Ebook from IG Library
Keywords: Supply and Operations Management; Quản lý cung ứng và vận hành ; Production management ; Operations management; Quản lý sản xuất; Quản lý hoạt động